Pengaruh Motivasi Dan Kompetensi Terhadap Kinerja Perawat Di Instalasi Paviliun Tandang Pada Rumah Sakit Umum Daerah Kabupaten Sumedang - Nining Kurniasih (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
The findings of this study prove all the hypotheses of this research, namely that there is an influence of work motivation and competence, either simultaneously or partially. The influence arising from the results of the study shows a positive direction, which means that better work motivation and good competence will improve the performance of nurses. Nurse motivation is a form of willingness to strive to achieve organizational goals by paying attention to efforts to satisfy several needs, as well as efforts to to improve and shape the knowledge, attitudes and behavior of employees so that these employees voluntarily try to work cooperatively with other employees to improve their performance.The effect of work motivation on the performance of nurses, to see if there is an influence between the motivational variables and the performance of nurses, the thing that needs to be done is to determine the hypothesis, based on the calculation results, H0 is rejected and H1 is accepted. This means that there is an influence between the motivation and performance of nurses. while the magnitude of the influence of motivation on the performance of nurses means that motivation increases, then the performance will increase.The effect of competence on the performance of nurses, the results of the calculation of H0 are rejected and H1 is accepted. This means that there is an influence between the competence and performance of nurses. To see the effect of motivation and competence on the performance of nurses simultaneously (combined), the magnitude of R Square can be used to see the magnitude of the influence of motivation and competence on the performance of nurses simultaneously or simultaneously. The magnitude of the influence of motivation and competence on the performance of nurses is jointly influenced by other factors, namely, training, compensation and others.The results of the calculation of the correlation between the variables studied using the SPSS software assistance program, it is known that the correlation value between motivation and competence variables shows that the relationship between variables is very strong. and the correlation of the two variables is significant, from the results of the path coefficient calculations obtained, it can be seen the magnitude of the influence of the hypothesized variables. variables outside the research variables affect the performance of nurses.